Author Correction: LSD1 modulates the non-canonical integrin β3 signaling pathway in non-small cell lung carcinoma cells. Issue 1 (December 2018) - Lim, So-Young; Macheleidt, Iris; Dalvi, Priya; Schäfer, Stephan; Kerick, Martin; Ozretić, Luka; Ortiz-Cuaran, Sandra; George, Julie; Merkelbach-Bruse, Sabine; Wolf, Jürgen; Timmermann, Bernd; Thomas, Roman; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.